Evaluasi Implementasi Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) Dengan Metode Design-Reality Gap - Gultom, Firstha Greacean; Khudri, Tubagus Muhamad Yusuf (Politeknik Ganesha Medan, 2024)
The Agency Level Financial Application System (SAKTI) is one of the e-government implementations that has a systemic and significant impact. Several previous studies have shown the unsuccessful implementation of SAKTI related to the implementation of the system.This research aims to evaluate the gap between design and reality in the implementation of SAKTI to obtain recommendations in order to mitigate the risk of failure of future system implementations. The research was conducted to the organizers of the SAKTI system, namely the developers and managers of the SAKTI modules. The resource persons were selected to represent the organization as structural leaders and responsible teams based on their involvement and active participation in the development and management of the SAKTI application. The research used a case study research strategy with a qualitative approach. Data/information collection from this research used techniques consisting of: observation, interviews, and literature review. The model used is the design-reality gap model supported by the concept of critical success factors/csfs in each checklist Information, Technology, Process, Objectives and Values, Staffing and Skills, Management and Structure, and Other Resources (ITPOSMO). The results show that the design-reality gap is 52.0 which falls into the category of e-government projects may fail unless there are actions to close the design-reality gap. The largest gap occurs in the staffing and skills dimension followed by the information, technology, management and structure, process, and goals, values and motivation dimensions. This suggests that the dominant factor of failure in SAKTI is socio-technical not just technical.